Advancing primary care: Establishing family medicine specialty in Tanzania - Eric L. Aghan; Henry Ziegler; Donatus R. Mutasingwa; Enica R. Massawe; Peter J. Wangwe; Dennis Lyakurwa; Muzdalifat Abeid; Riaz Ratansi; Nadeem Kassam; Esther Johnston (AOSIS, 2023)
Family medicine has existed as a training pathway through a private university in Tanzania since 2004. As global calls have increased to embrace primary health care as a pathway to ensuring universal health coverage, so has Tanzania recently turned to explore family medicine as a specialty to improve access to comprehensive, high-quality healthcare for her entire population. This article outlines ongoing efforts to define competencies and skills of a family medicine physician in Tanzania, engage government support and open the first public university training programme for family medicine postgraduate education.